Catastrophic fracture of the middle phalanx following intra‐articular ethanol injection for facilitated proximal interphalangeal joint ankylosis. (24th October 2022) - Arndt, Stefanie; Katzman, Scott A.; LaPorte, Alexandra D.; Spriet, Mathieu; Maglaty, Marisa A.; Murphy, Brian G.; Galuppo, Larry D.
Summary: Facilitated ankylosis using intra‐articular ethanol has been reported as a viable alternative to proximal interphalangeal (PIP) arthrodesis for owners with financial constraints or reservations regarding the invasiveness of surgical arthrodesis. An 18‐year‐old gelding presented for a left front leg lameness (Grade 4/5 on the AAEP scale) localised to the pastern region. Radiographs revealed severe osteoarthritis of the proximal interphalangeal joint (PIJ). Facilitated ankylosis of the PIJ with 95% alcohol was elected. The horse presented 6 weeks later with a significant worsening of the lameness, swelling of the pastern region and was noticed with the toe elevated off the ground when transiently weight bearing. Radiographs revealed a comminuted fracture of the middle phalanx. The horse was humanely euthanised. Necropsy revealed a severe chronic closed comminuted fracture of the middle phalanx with partially devitalised bone. Potential aetiologies are a decreased bone quality prior to alcohol injection, or that the desensitisation due to the alcohol injection could have resulted in an overuse by the horse or a traumatic accident. While previously unreported, veterinarians should educate owners that catastrophic fracture is an unlikely but possible complication following intra‐articular ethyl alcohol injection.